Joint public procurement as a tool for European Union industrial policy - Francesco Nicoli; Roel Beetsma (Bruegel, 2024)
Joint procurement is an important tool that is currently under-exploited at European Union level. It can greatly enhance the effectiveness of public spending in Europe, achieving greater coherence between spending across different countries, exploiting monopsony power, producing economies of scale, reducing downward competition between public authorities, improving the single market and producing a degree of solidarity without resulting in redistribution between EU countries. The EU has already implemented several joint-procurement projects, including for COVID-19 vaccines, gas supplies and ammunition for Ukraine. These previous experiences can work both as a blueprint and as a pilot for larger-scale actions. Joint procurement could be particularly relevant in sectors with substantial economies-of-scale and industry-government ties, such as defence. Despite some degree of political opposition, experimental public opinion studies have shown consistently that joint procurement in such areas can strongly improve public support for EU-level action. Measures that could expand European joint procurement in a politically sustainable way include the use of framework contracts, which allow for ad-hoc commitments tailored to the needs of different EU countries; reporting by countries of their future large public procurement plans as a part of the European Semester so that the European Commission could propose coordinated actions if necessary; and the use of staggered contracting and multiple-award strategies, which can ensure a level playing field among companies of similar market power, promoting market-building and supporting the entry of new competitors.
Keywords: 330; eu governance